Enhance Security of Bank CKPN Value with the Implementation of PSAK No 50 and 55 - Mulkanuddin Ritonga (Budapest International Research and Critics University, 2022)
This study aims to analyze the application of PSAK 50/55 on financial instruments and the presentation of disclosure/ recognition and measurement that focuses on the calculation of CKPN conducted by PT. Bank of North Sumatra. This research was conducted with a descriptive method of multi-purpose credit PT. Bank of North Sumatra with interview staff, and data reports. And research literature is available from the company and other supporting data. The results showed that PT. Bank Sumut has applied PSAK 50/55 appropriate standards that focus on calculating CKPN, accounting maintenance carried out by good companies that the financial reports produced are reliable for customers and stakeholders.